Post-colonoscopy colorectal cancer (PCCRC) rates vary considerably depending on the method used to calculate them: a retrospective observational population-based study of PCCRC in the English National Health Service. Issue 8 (21st November 2014) - Morris, Eva J A; Rutter, Matthew D; Finan, Paul J; Thomas, James D; Valori, Roland
Abstract : Objective: Post-colonoscopy colorectal cancer (PCCRC) is a key quality indicator of colonoscopy. This study compares methods for defining PCCRC rates, proposes a new method of calculating them and quantifies them across the English National Health Service (NHS). Design: This retrospective observational population-based study involved all individuals with a first primary diagnosis of colorectal cancer made between 2001 and 2010 and treated in the English NHS. Previously published methods for deriving PCCRC rates were applied to the linked routine health data for this population to investigate the effect on the rate. A new method, based on the year of the colonoscopy rather than colorectal cancer diagnosis, was then used to calculate PCCRC rates. Results: Of 297 956 individuals diagnosed with colorectal cancer, a total of 94 648 underwent a colonoscopy in the 3 years prior to their diagnosis. The application of the published methods and exclusion criteria to the dataset produced significantly different PCCRC rates from 2.5% to 7.7%. The new method demonstrates that PCCRC rates within 3 years of colonoscopy (without exclusions) decreased in the English NHS over 8 years, falling from 10.6% to 7.3% for colonoscopies performed in 2001 and 2007 respectively. Conclusions: The method used to determine PCCRC rates significantly affects findings with potential to substantially underestimate rates. To enable international benchmarking there needs to be a standardised method for defining PCCRC. This study proposes a new methodology using colonoscopy as a denominator and between 2001 and 2007 this method indicated an 8.6% PCCRC rate across the English NHS. It also demonstrated PCCRC rates have fallen over time.